Retrospective study on feline heart disease in University Veterinary Hospital, Universiti Putra Malaysia (UVH-UPM) from 2013-2015 - Ahmad, Zakaria (2016)
This restrospective study conducted in UVH-UPM revealed that the overall prevalence of cats diagnosed with heart disease was 1% (n=155/15,493) with an increased trend over the period of 3 years (2013-2015). The mean age of feline heart disease patient was 5.2 years old (age range, 2-month to 20-year-old), more often seen in male (57%) compared to female (43%) cats. The two most common breeds presented with heart disease were Domestic Shorthair (54%) and Persian (26%) cats. Ten out of 155 cats diagnosed with heart disease were asymptomatic whereas the remaining (145 cats) patients were presented with varies clinical sign such as congestive heart failure. The acquired heart disease were often diagnosed compared to the congenital heart disease. Among the acquired heart diseases, hypertrophic cardiomyopathy (HCM) has the highest prevalence at 47%, followed by dilated cardiomyopathy (DCM) (18%), restrictive cardiomyopathy (RCM) (15%), and other types of heart disease (11%) (Consist of pericardial effusion, aortic insufficiency, heart base tumour, and feline heartworm disease), myocarditis (7%), and congenital heart disease (2%) (Atrial Septal Defect (ASD) and Ventricular Septal Defect (VSD)). These feline heart disease patients were stage using and the New York Heart Association (NYHA) Classification. Majority of the feline heart patient in this study were in Class II (n=52) and Class III (n=67), followed by Class IV (n=26), and minority was Class I (n=10). Echocardiography remains the best diagnostic tools compared to radiography, where normal size of heart does not rule out heart disease in cats.